Adoption, benefits and challenges of strategic management accounting practices: evidence from emerging market / Yap Kiew Heong Angeline ...[et al.] - Yap, Kiew Heong Angeline; Lee, Teck Heang; Said, Jamaliah; Yap, Saw Teng (Faculty of Accountancy, 2013)
Strategic Management Accounting (SMA) techniques were developed to provide information appropriate for decision making in changing internal and external environments. However, studies in the developed countries demonstrated that firms were slow to adopt such techniques. This study aims to identify the types of management accounting practices currently adopted by Malaysian companies. Subsequently, this study is interested to identify benefits received from the current management accounting practices and challenges in implementing SMA techniques. Based on 118 responses received, the findings revealed that 55.1% of the sample companies adopted ten out of forty five management accounting techniques. This percentage indicates that the adoption rates for management accounting practices by Malaysian companies were relatively lower than other countries. Analysis of the findings also showed that the top five management accounting techniques used were related to traditional management accounting techniques. Those techniques were budgeting, breakeven analysis, variance analysis and cash flow. However, some companies started to adopt SMA techniques such as product profitability analysis, activity based costing, balanced scorecard and benchmarking practices.